Insitu tubularisation of skin graft for re‐do hypospadias repairment. Issue 2 (5th January 2022) - Atan, Ali; Turkyilmaz, Zafer; Karabulut, Ramazan; Kaya, Cem; Polat, Fazli; Sonmez, Kaan
Abstract: We describe in situ skin graft tubularisation over the urethral catheter. This tehnique allows preparation of a urethral tube on a fixed line and suture the wound sides comfortably while preventing the movement of the graft.